Does digital village construction promote agricultural green total factor productivity? An empirical study based on China's Provincial panel data - Lingling Xu; Danai Tanamee; Suppanunta Romprasert (Economies, 2025)
Based on endogenous growth theory and technological innovation theory, this paper uses panel data from 30 provinces in China from 2011 to 2022 to investigate the impact of digital village construction on agricultural green total factor productivity (AGTFP). AGTFP was measured by the EBM-GML method, and mediated effects and heterogeneity analysis were used to reveal its conduction pathway. The findings are as follows: (1) AGTFP showed an overall upward trend during the sample period, and most provinces peaked in 2018. Among them, the AGTFP index value of the eastern coastal provinces (such as Tianjin and Beijing) is between 1.059 and 1.129, maintaining the leading position. The western region fluctuates greatly; e.g., the AGTFP value of Qinghai Province fluctuates between 0.915 and 1.047. (2) Digital village construction significantly improves AGTFP by promoting green technology progress (coefficient 0.105, significant at the 5% level) but has no significant impact on technical efficiency. (3) Agricultural informatization (coefficient 0.040, significant at the 5% level) and rural human capital (coefficient 0.115, significant at the 5% level) are important intermediary channels for digital village construction to affect AGTFP. (4) Regional heterogeneity analysis showed that the effect of digital village construction in the eastern region (coefficient 0.151, significant at the 5% level) and the southern provinces (coefficient 0.170, significant at the 1% level) was more significant. The digital village construction in the main producing areas (coefficient 0.113, significant at the 1% level) also significantly promoted AGTFP. Based on the research results, it is suggested that the promotion and application of digital technology be strengthened, the land transfer system improved, an agricultural information platform built, rural human capital improved, and regional differentiated development strategies implemented.
Keywords: 330; digital village construction; agricultural green total factor productivity; agricultural informatization; rural human capital; regional heterogeneity